Skeletal Class II Malocclusion with Maxillary Constriction - A Comprehensive Treatment Approach - Yezdani, A. Arif; Fathima , Jabeen (New Horizons in Medicine and Medical Research Vol. 12, 2022)
A comprehensive strategy combining the use of rapid palatal expansion appliance followed by fixed appliance therapy can effectively be used to treat a bilateral maxillary posterior crossbite with severe skeletal Class II malocclusion during the growth phase, as demonstrated in this case report. A 14-year-old boy presented with a severe skeletal Class II malocclusion with an orthognathic maxilla, retrognathic mandible and a high mandibular plane angle with an Angle’s Class II division 1 subdivision malocclusion with maxillary constriction, increased overjet, deep bite and severe crowding of maxillary and mandibular incisors. The objectives were to first employ an orthopedic phase to expand the constricted maxilla to facilitate normal growth of the mandible and then continue with an orthodontic phase to correct the tooth size-arch length discrepancies in the maxillary and mandibular dental arches. To correct the bilateral posterior crossbite, a banded rapid palatal expansion appliance was initially used, and then maxillary and mandibular first premolars were extracted and Roth’s pre-adjusted edgewise appliance therapy (0.022 x 0.28-inch slot) was strapped up to address the severe tooth size-arch length discrepancy. The patient’s soft tissue profile and dentofacial esthetics improved dramatically post treatment together with increased self-confidence and enthused self-esteem.